STEM Knowledge Awareness among Higher Secondary School Students - P. Tamil Selvan; G. Kalaiyarasan (Journal of Education for Sustainable Development Studies, 2024)
Educators in the twenty-first century need to think of innovative ways to engage and prepare students for current and future challenges while cultivating an interest among students in STEM disciplines. This study sought to investigate students’ STEM knowledge awareness and the level of STEM knowledge awareness among higher secondary school students. Only higher secondary level students which engaged in imparting higher secondary school education in the class of twelfth included. The study focused on the higher secondary level education with Tamil Nadu state board education. This study main objectives were to find out the level of STEM knowledge awareness among higher secondary school students, to find out whether there is any significant difference in STEM knowledge awareness of higher secondary school students owing to differences in Parents’ Educational status and to find out whether there is any significant difference in STEM knowledge awareness of higher secondary school students owing to differences in Type of school. This study employed a survey measure design and a simple random sampling technique. An instrument such as standardized tool STEM knowledge awareness was used for data collection from the sample of 204 higher secondary school students around Karaikudi in Sivaganga. Data were taken using Questioner. Data were analyzed using descriptive analysis. The tool comprises 2 sections such as the demographic profile, and STEM knowledge awareness (16 statements). Raw data from the questionnaires was digitised, manually coding them using SPSS statistical analysis software. The statements under the usage of the Internet were measured using a 5-point Likert scale consisting of 5 Strongly Agree, 4 Agree, 3 Neutral, 2 Disagree, and 1 Strongly Disagree. The study’s findings reveal no significant difference and a favourable level of awareness of STEM knowledge among higher secondary school students.